Does Sustainability Reporting Enhance Firm Value? The Moderating Role of Profitability in Indonesia's Energy Sector - Lukman Dahlan; Fitrawansyah Fitrawansyah; Rahayu Alkam; Wina Ayudia Akbar (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
This study aims to analyze the effect of sustainability report disclosure based on GRI Standards 2021 on firm value, and to examine the moderating role of profitability in this relationship. The population comprises energy sector companies listed on the Indonesia Stock Exchange (IDX) in 2023–2024. Using purposive sampling, 34 companies were selected as the final sample. The independent variable was measured through the Sustainability Report Disclosure Index (SRDI) based on 141 GRI Standards 2021 indicators, firm value was proxied by Tobin's Q, and profitability was measured using Return on Assets (ROA). Data were analyzed using multiple regression and Moderated Regression Analysis (MRA). Results show that sustainability report disclosure has a positive and significant effect on firm value. Profitability significantly moderates this relationship negatively, indicating that for highly profitable firms, the marginal effect of sustainability disclosure on firm value diminishes. These findings are consistent with signaling theory, where sustainability reports serve as strategic signals that are more relevant for firms with low-to-moderate profitability.